Diagnostic Role of Systemic Inflammatory Indices in Infants with Moderate-to-Severe Hypoxic Ischemic Encephalopathy - Ceran, Burak; Alyamaç Dizdar, Evrim; Beşer, Esra; Karaçağlar, Nazmiye Bengü; Sarı, Fatma Nur (American Journal of Perinatology, 2021)
Background When the newborn brain is exposed to hypoxia, as in hypoxic ischemic encephalopathy (HIE), it causes an inflammatory response. A wide variety of inflammatory markers are therefore used in the diagnosis of HIE.Objective We aimed to determine the diagnostic role of systemic inflammatory indices in infants with moderate-to-severe HIE. We have also investigated the effect of hypothermia treatment over those indices.Study Design A retrospective cohort study of infants suffering from moderate-to-severe HIE was conducted in a tertiary-level neonatal intensive care unit between September 2019 and March 2021. Systemic inflammatory indices including systemic immune-inflammation index (SII), pan-immune-inflammation value (PIV), systemic inflammation response index (SIRI), neutrophil-to-lymphocyte ratio (NLR), platelet-to-lymphocyte ratio (PLR), and monocyte-to-lymphocyte ratio (MLR) were calculated for infants with HIE and controls at baseline, and after therapeutic hypothermia in those with HIE.Results A total of 103 infants (53 in the HIE group and 50 in the control group) were included in the study. Median gestational ages (GA) were 39 (37–40) and 38 (37–39) weeks, and median birth weights (BW) were 3,165 (2,890–3,440) and 3,045 (2,850–3,460) g in the HIE and control groups, respectively. GA, BW, mode of delivery, and gender of infants were similar between the groups. Infants in the HIE group had significantly higher NLR (p = 0.001), SII (p = 0.001), PIV (p = 0.001), and SIRI (p = 0.004) values when compared with the control group. Those indices decreased significantly after hypothermia treatment in the HIE group. Areas under curve for NLR, PLR, MLR, SII, SIRI, and PIV to predict HIE were found to be 0.808, 0.597, 0.653, 0.763, 0.686, and 0.663, respectively. Cutoff values having a good ability to predict HIE for SII and NLR were 410 and 1.12. Elevated NLR level above 1.12 was found to be an independent predictor for HIE, as revealed by multivariate analyses. No associations were found between systemic inflammatory indices and amplitude-integrated electroencephalography (aEEG) patterns, presence of seizures, and death.Conclusion Systemic inflammatory indices may represent reliable and readily available predictors of HIE risk. NLR seems to be an independent factor in diagnosing moderate-to-severe HIE.Key Points
Keywords: asphyxia; hypoxic ischemic encephalopathy; neutrophil-to-lymphocyte ratio; newborn; systemic inflammatory indices